Desempeño laboral y eficiencia administrativa en la Dirección Distrital 05D06 Salcedo - Salud en el año 2014. Propuesta de un manual por procesos. - Herrera Corrales, Lucila de los Angeles (2015)
This study aimed to diagnose the current situation regarding work performance measurement of the administrative staff of the District Health Directorate-05D06 Salcedo. The main objective was to determine the importance of performance evaluation with a focus on job skills in workers who make up the institution. In the research process we were able to see the importance of performance evaluation since this way you can make the necessary corrections given to the failures that are occurring, since the results that have occurred in previous research indicates that is great positive influence on the performance of workers of the institution. The functions they perform different employees are not coordinated, which allows for a duplication of tasks and various other problems by poor organization. The standardization process is a necessity in the District Health Directorate-05D06 Salcedo, one considers that at the institutional level there are tasks to be carried out by officials of the entity to meet the objectives of efficiency of organizational culture through a manual process with which improvement is sought thereof. Since is used as a tool to improve the institution manual processes, because by this manual seek to collect a thorough and detailed all instructions to be follow to perform an activity in a simple way, without fear of mistakes.